Urolithiasis - a chronic and recurrent disease in a girl with multiple congenital anomalies and cerebral palsy- case report - E. Wajszczuk; M. Szymanek-Szwed; J. Samotyjek; K. Jobs; B. Jurkiewicz (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2019)
Urolithiasis is a disease unit more common in adult patients. However in the pediatric population it is also animportant clinical problem due to high risk of recurrence in the patient's life among others. Hyperkalciuria, hyperuricemia, hyperoxaluria and cystinuria secondary to metabolic disorders promote stone formation.The aim of this study is the presentation of a case of a girl with multiple congenital anomalies, bilateral staghornurolithiasis and bladder stones developing in the course of hypercalcemia.The patient was diagnosed with urolithiasis at the age of 2 months. The course of the disease in her case is characterized by extremely frequent recurrences and numerous urinary tract infections of various aetiology, includinghigh-resistant bacterial strains. These infections were often turbulent and required hospitalization. Due to the extentof urolithiasis, invasive treatment was necessary, both in the lower and upper urinary tract. Endoscopic techniques(transurethral cystolithotrypsy and ureterorenoscopy) were used in urinary bladder and ureter urolithiasis. Renaldeposits were removed by the use of open access surgery (pyelolithotomy with intrarenal lithotrypsy).Although the ongoing development technology and miniaturization of equipment have allowed and popularizedminimally invasive treatment of urolithiasis, some exceptional cases still require surgical treatment with open surgery.The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocolwas approved by the Local Ethics Committee (LEC) of all institutions. No conflict of interest was declared by the authors.